2018
DOI: 10.1186/s12985-018-1064-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of human adenovirus associated with acute respiratory infections in Cameroon from 2011 to 2014

Abstract: BackgroundHuman adenoviruses (HAdVs) cause a wide range of diseases worldwide, including respiratory infections. Studies on HAdV molecular epidemiology are limited in Cameroon. The purpose of this study is to document the different types HAdV circulating in Cameroon in children with acute respiratory infections.MethodsNasopharyngeal swabs were collected from 811 children under 15 years from 2011 to 2014. The HAdV detection was assessed by semi-quantitative generic PCR r-gene®. The HAdV-positive samples were ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
(36 reference statements)
7
17
2
Order By: Relevance
“…Most of the HAdV‐positive infections detected in this study were HAdV‐C followed by HAdV‐B. A report from Cameroon found that HAdV‐B infections were more common and severe than HAdV‐C 33 . On the contrary, studies conducted in Egypt and Senegal were consistent with our findings showing a predominance of HAdV‐C 10,34 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Most of the HAdV‐positive infections detected in this study were HAdV‐C followed by HAdV‐B. A report from Cameroon found that HAdV‐B infections were more common and severe than HAdV‐C 33 . On the contrary, studies conducted in Egypt and Senegal were consistent with our findings showing a predominance of HAdV‐C 10,34 .…”
Section: Discussionsupporting
confidence: 91%
“…This study has discovered that HAdV seems to increase the risk of low oxygen saturation and the duration of oxygen support in the pediatric environment which is in line with other reports showing that HAdV is associated with severe clinical manifestations 30,31 . In Africa, HAdV was associated with influenza‐like illnesses in several countries like Morocco, Egypt, Cameroon, and Senegal 13,32‐34 . However, the severity of respiratory infections was variable.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations